Report on consent in international prisoner transfers - Mulgrew, Roisin (2010)
This report, presented to the Council of Europe's Council for Penological Cooperation (PC-CP)(66th Meeting, 8-10 December 2010), outlines the different approaches adopted by the various treaties governing prisoner transfers in relation to consent, and analyses the human rights implications of these approaches.